The Name Game: Archaeologies of the Land of the Bible, Eretz Yisrael, the Holy Land and Palestine. Issue 1 (2nd January 2019) - Nathanson, Michael
ABSTRACT: In post-modernist terms, archaeology, like history, is not practiced for itself but for someone or something. That much is clear with the archaeology of the c is -Jordanian region of the Near East where it has served to sustain anthropological-ethnological models driven by biblical and nationalistic-based theories. Words, terms, labels and names have meanings that not infrequently are consequential thus, constructing an archeology-abetted past of spaces named Holy Land, Eretz Yisrael and Land of the Bible belies the discipline's claim to scientific neutrality. No less, naming the c is -Jordanian territories of the Bronze and Iron Ages a "Palestine" is anachronistic and not uniformly acceptable. As long as Archaeology is tasked with proving the veracity of ancient epigraphy and texts and legitimizing claims of ancestral privilege and ur-ownership of ancient lands, the more glaring its failure and the greater the impediment to settling the Israeli-Palestinian Conflict.